A METHOD FOR QUANTITATIVE DESCRIPTION OF BIOMEDICAL IMAGES BASED ON SUPERPIXEL DICTIONARIES - V. A. Liauchuk; V. A. Kovalev (Informatika)
With this study, a method for quantitative description of biomedical images based on splitting the target image into superpixels followed by categorization using precalculated superpixel dictionaries is proposed. The method has been tested on the tasks of recognition of biomedical images of three types: lung CT images, histology images of ovary and thyroid tissues. The results of the experiments performed suggest that the method proposed may provide recognition performance comparable or better than when using conventional methods of texture description.